PERAN PENGUSAHA MEBEL DALAM MEMENGARUHI PROSES PEMBUATAN PERATURAN DAERAH KABUPATEN JEPARA NOMOR 17 TAHUN 2013 TENTANG PERLINDUNGAN INDUSTRI - ABDUS SOMAD SOFARI, ABDUS SOMAD SOFARI (Program Magister Ilmu Politik, Universitas Diponegoro, 2014)
The direct involvement of employers in the discussion of public policy, introduced and contributed to the draft laws and regulations are very influential in the smooth running of the business into the background of this research. The problem that arises: How does the role of the entrepreneur in the making of furniture Jepara District Regulation No. 17 of 2013 on the Protection of Industrial? What factors are affecting the role of entrepreneurs in the manufacture of furniture Jepara District Regulation No. 17 of 2013 on the Protection of Industrial? The purpose of research to identify the role of the entrepreneur in the making of furniture Jepara District Regulation No. 17 of 2013 on the Protection of Industrial. To determine the factors that affect employers in manufacturing furniture Jepara District Regulation No. 17 of 2013 on the Protection of Industrial. Efforts to address concerns and objectives of this research is done by using a qualitative analysis. Sobyek research is the Association of Indonesian Rattan Furniture And Crafts (DPD AMKRI), Parliament, professional associations, NGOs and other community groups involved in the making of public policy. The results showed furniture producers have a role in three parts, namely the issue of policy is a source of initiative emergence of the issue Protection Industry. The role of furniture producers in the consultant to provide information industry conditions in Jepara. The role of furniture producers on Harmonization approve the change of the original legislation Title Industry Furniture Industry and its becoming Protection A revised. Factors affecting the role of entrepreneurs in the manufacture of furniture Jepara District Regulation No. 17 of 2013 on the Protection of Industrial include: concern over threatened furniture business continuity, maintain image